The Influence of Product Quality, Income, and Price on The Purchase Intention of Electric Vehicles in Denpasar City - Putu Risma Yuliana; Surya Dewi Rustariyuni (International Journal of Economics, Management and Accounting, 2025)
Global warming triggers various environmental issues such as rising sea levels and extreme weather pattern changes. Fuel-powered vehicles are considered the main contributors to global warming and air pollution. The government’s commitment to sustainable development is evident through the promotion of electric vehicles and the development of charging station infrastructure as regulated by Presidential Regulation (Perpres) Number 55 of 2019. This study aims to examine the simultaneous and partial effects of product quality, income, and price variables on the purchase intention of electric vehicles in Denpasar City. The sample determination used a non-probability sampling technique with purposive sampling method involving 100 respondents. Data collected were analyzed using multiple linear regression analysis. The results indicate that product quality has a positive and significant effect on purchase intention, income has a positive and significant effect on purchase intention, and price has a negative and significant effect on purchase intention.